Carbon sequestration in an expanded lake system during the Toarcian oceanic anoxic event - Xu, W; Ruhl, M; Jenkyns, H; Hesselbo, S; Riding, J; Selby, D; Naafs, B; Weijers, J; Pancost, R; Tegelaar, E; Idiz, E (Springer Nature, 2017)
The Early Jurassic Toarcian oceanic anoxic event (∼183 Ma) was marked by marine anoxia–euxinia and globally significant organic-matter burial, accompanied by a major global carbon-cycle perturbation probably linked to Karoo–Ferrar volcanism. Although the Toarcian oceanic anoxic event is well studied in the marine realm, accompanying climatic and environmental change on the continents is poorly understood. Here, utilizing radioisotopic, palynological and geochemical data from lacustrine black shales, we demonstrate that a large lake system developed contemporaneously with the Toarcian oceanic anoxic event in the Sichuan Basin, China, probably due to enhanced hydrological cycling under elevated atmospheric pCO2 . We attribute increased lacustrine organic productivity to elevated fluvial nutrient supply, which resulted in the burial of ∼460 Gt of organic carbon in the Sichuan Basin alone, creating an important negative feedback in the global exogenic carbon cycle. We suggest that enhanced nutrient delivery to marine and large lacustrine systems was a key component in the global carbon cycle recovery during the Toarcian oceanic anoxic event and acted to shorten the duration of the recovery of global δ13C values.